Survey of dental diseases in Crioulo breed horses reared in an extensive farming system - Leite, C. T. [UNESP]; Duarte, C. A.; Mozzaquatro, F. D.; Mistieri, M. L. A.; Machado, I. R. L.; Porciuncula, M. L.; Leoni, I. S.; Dowich, G.; Goss, G. C.; Santini, A. P.; Pereira, E. P. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The present study aimed to identify and quantify dental diseases in Crioulo horses reared exclusively under extensive farming conditions. In total, 254 Crioulo horses were evaluated, that were reared exclusively in native pastures with predominantly Eragrostis plana (Annoni grass). The animals were divided into three groups according to age: three to five years (G1), six to 12 years (G2), and 13 to 26 years (G3). In total, 46.1% of the animals in G1, 63.8% in G2, and 82.3% in G3 had two or more incisor disorders; 37.5% in G1, 52.5% in G2 and 45.5% in G3 had two or more disease findings in the canines; and 28.9% in G1, 35.4% in G2, and 64.7% in G3 had four or more disease findings in the second, third, and fourth premolars and molars. However, dental calculus was observed in 90.5% of G2 animals, whereas in G3, the occurrence rate of excessive enamel points and calculus was 82.4%. Although all of the horses studied were reared in an extensive farming system, dental changes were very common in the Crioulo breed reared under these management conditions.
Keywords: horses and crioulo breed; dental diseases